A Hybrid Scheduling Mechanism Based on Agent Cooperation Mechanism and Fair Emergency First in Smart Factory - Sehrish Malik; DoHyeun Kim (IEEE Access, 2020)
Smart factory also known as smart manufacturing is an emerging field with the revolution of industry 4.0. With the help of all these concepts, the smart factory integrates the manufacturing assets and represents industrial networks. In this paper, we focus on integrated solutions for smart factory concerns; by proposing an efficient task management mechanism based on an efficient and resource-aware scheduling scheme named as ACM-FEF. The scheduling algorithm used for the efficient task management is hybrid of the two scheduling approaches as agent cooperation mechanism (ACM) and fair emergency first (FEF) scheduling scheme. ACM is a decentralized scheduling approach which focuses on the production maximization goals per machine, and also pays attention to the production goals of all the machine networks involved in the smart factory. FEF scheduling scheme focuses on minimizing the tasks starvation rate and maximizing the machine utilization by efficiently using the machine slots. The proposed hybrid mechanism aims to efficiently plan tasks execution, maximize machines' resource utilization, maximize productivity, minimize production delays, efficiently handle exceptions and efficiently control smart factory actuators.